An Optimised Method for Routine Separation and Quantification of Major Alkaloids in Cortex Cinchona by HPLC Coupled with UV and Fluorescence Detection. Issue 5 (31st March 2017) - Holmfred, Else; Cornett, Claus; Maldonado, Carla; Rønsted, Nina; Hansen, Steen Honoré
Abstract: Introduction: Authentication of herbal products to ensure efficacy and safety require efficient separation and quantification of constituents. Standard assays for Cinchona bark used for the treatment of malaria and production of quinine, either use only spectrophotometry to detect two pairs of diastereoisomers of quinine and cinchonine type alkaloids ( European Pharmacopoeia, Ph.Eur.) or liquid chromatography primarily optimised for detection of the four major alkaloids. However, numerous minor alkaloids occur in Cinchona and related species and efficient separation including gradient elution is necessary in order to obtain the full pattern of constituents in bark samples. Objective: To develop an optimised HPLC method for separation and quantitative analysis of the four major alkaloids in Cinchona bark using UV detection. Methodology: Dimethyl sulphoxide (DMSO) extracts of 50 mg of pulverised barks were prepared using ultrasonication. The chromatographic separation was performed on an XB‐C18 column packed with 2.6 μm particles. Gradient elution using an ammonium formate buffer and methanol as organic modifier over 26 min was based on non‐chiral separation of the diastereoisomers and the high solvent selectivity of methanol. Post column UV detection was performed at 250 nm and 330 nm. Fluorescence detection was performed using 330 nm for excitation and 420 nm for emission. Results: The optimised HPLC method facilitates efficient separation and quantification of the four major alkaloids in 26 min with a limit of quantification of 5 μg/g from 50 mg bark sample. Conclusion: The optimised HPLC method offers a simple and efficient quantification of the four major alkaloids. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : Authentication of herbal products to ensure efficacy and safety require efficient separation and quantification of constituents. Numerous minor alkaloids occur in Cinchona bark used for the treatment of malaria and production of quinine. An optimised HPLC‐UV method facilitates efficient separation and quantification of the four major Cinchona alkaloids in 26 min with a limit of quantification of 5 μg/g from 50 mg bark sample.